Imagens da Espanha cindida: história e memória de mulheres na Trilogia de la Memoria, de Josefina Aldecoa - Talita Oliveira Almeida (2023)
In order to properly comprehend the Trilogy of Memory in the works by Josefina Aldecoa, this paper will examine historical events related to the 20th-century fight for women's rights in the Spanish context and how they impacted the various character points of view in the three books. In order to accomplish this, we recognize the ways in which the female characters reflect the author's individual and collective memory representations. In addition, we consider the portrayal of Spain by the main characters over the three distinct periods of the trilogy—the Republic, the Civil War, Francoism, and Exile.